Intensi Perilaku Berwisata Alam Pasca Vaksinasi Covid-19 - Hakim, Imam Nur; Eddyono, Fauziah; Abdullah, Syahfirin (JURNAL MASTER PARIWISATA; Volume 09, Nomor 01, Juli 2022DO - 10.24843/JUMPA.2022.v09.i01.p10, 2022)
The Covid-19 pandemic has had a destructive impact that has changed Indonesia’s tourism sector. One of the changes is the shift in preferences and behavior of tourists who switch to natural destinations, especially after the Covid-19 vaccination. This study aims to determine the factors that can trigger the emergence of behavioral intentions for nature tourism after the Covid-19 vaccination, especially in DKI. Jakarta has the highest infection rate, cure, and recipient of the Covid-19 vaccine in Indonesia. This study empirically applies the theory of planned behavior (TPB) to 156 respondents. Using Structural Equation Modeling (SEM), data processing and analysis tests found four significant and one insignificant correlation. Attitudes and subjective norms significantly influence the intention of nature tourism after the Covid-19 vaccination. Even subjective norms empirically can also influence the emergence of attitudes and perceived behavioral control of nature tourism behavior. However, the perceived behavioral control of nature tourism behavior cannot trigger the emergence of the nature tourism behavioral intention of DKI. Jakarta even though they have been vaccinated. Keywords: covid-19, theory of planned behavior (tpb), tourism, tourism behavioral intention, vaccine.